Fear and Its Relationship with Backstroke Leaning in Sophomore College of physical Education and Sport Sciences Students - Nazim, Mohammed; Sabah, Wafaa (Journal of Physical Education, 2019)
The research aimed at identifying the relationship between fear and learning backstroke swimming in sophomore students of physical education and sport sciences college. The researchers used the descriptive method on (12) students for pilot study and (50) students for the main experiment. The researchers used the (25m) artistic performance test of backstroke swimming for measuring backstroke swimming as well as fear from water scale that consisted of (20) items. The results showed significant relationship between fear and backstroke swimming on college of physical education and sport sciences.